2018
DOI: 10.1039/c8cp04535f
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of solid–liquid interfaces using scaled charges: rutile (110) surfaces

Abstract: Electronic continuum correction (ECC) has been proven to bring significant improvement in the modeling of interactions of ions (especially multivalent) in aqueous solutions. We present a generalization and the first application of this approach to modeling solid-liquid interfaces, which are omnipresent in physical chemistry, geochemistry, and biophysics. Scaling charges of the top layer of surface atoms makes the existing solid models compatible with the ECC models of ions and molecules, allowing the use of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(70 citation statements)
references
References 83 publications
3
66
0
Order By: Relevance
“…Another cause of the deviations is the use of full charges. These do not take into account the dielectric screening of the medium and frequently result in an over-prediction of ion-adsorption 37,38 and ion-pairing. 39,40 In an attempt to account for this screening, the Electronic Continuum Correction (ECC) theory states that the charges should be scaled by a factor between 0.75 and 0.85.…”
Section: Introductionmentioning
confidence: 99%
“…Another cause of the deviations is the use of full charges. These do not take into account the dielectric screening of the medium and frequently result in an over-prediction of ion-adsorption 37,38 and ion-pairing. 39,40 In an attempt to account for this screening, the Electronic Continuum Correction (ECC) theory states that the charges should be scaled by a factor between 0.75 and 0.85.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some of us 22 have developed TiO 2 force field of a standard molecular-mechanical form with electrostatic, Lennard-Jones and bonded interactions, which was further modified by scaling of charges according to the electronic continuum correction theory. 23 The force field of ref. 22 was parametrized to fit available experimental data on crystal structures and water adsorption enthalpies.…”
Section: Force Field Parameterizationmentioning
confidence: 99%
“…In this study, the non-bonded LJ parameters and bonded parameters for both the solid phase and the aqueous electrolytes are the ones published in ref. 32. Furthermore, surface charges around the hydroxyl group bonded to the Ti site and the protonated oxygen bridge resulting from water dissociation described by eqn (1) were taken from ref.…”
Section: Edl Properties In the Non-reactive Frameworkmentioning
confidence: 99%
“…Within this idea, numerous in silico experiments in the MD framework were performed to reveal structure-property relationships for the rutile-(110) TiO 2 /water system. 8,[28][29][30][31][32][33] Although the hydroxylation of the surface was (i) explicitly considered in classical, non-reactive MD approaches for modeling charged surfaces, 8,[33][34][35] or (ii) dynamically evolving using a reactive force field to analyze electrostatic properties of the rutile-TiO 2 /water system 31 or to quantify the surface reactivity of different TiO 2 polymorphs, 36 a defect-free titania surface interacting with bulk water or aqueous electrolyte is the common assumption to both classical MD studies and the ones performed using a reactive force field. Recently, it was reported that dissociation kinetics of a water molecule was around 20 times faster on a defective rutile-(101) TiO 2 surface than on the defect-free surface.…”
Section: Introductionmentioning
confidence: 99%